2015
DOI: 10.1007/s11356-015-5989-y
|View full text |Cite
|
Sign up to set email alerts
|

Sediment cores from kettle holes in NE Germany reveal recent impacts of agriculture

Abstract: Glacial kettle holes in young moraine regions receive abundant terrigenous material from their closed catchments. Core chronology and sediment accumulation were determined for two semi-permanent kettle holes, designated RG and KR, on arable land close to the villages of Rittgarten and Kraatz, respectively, in Uckermark, NE Germany. Core dating ((210)Pb, (137)Cs) revealed variable sediment accretion rates through time (RG 0.4-23.1 mm a(-1); KR 0.2-35.5 mm a(-1)), with periods of high accumulation corresponding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The sedimentation rates previously estimated from two KH that are part of the present study (KH258 and KH807; Kleeberg et al, 2016) correspond to an average age of 15-30 years prior to this study in the upper 5 cm and to 50-100 years at 20 cm depth. These values are in line with previous studies in the area, which concluded that the sedimentation rate increased from 1-2 mm y -1 prior to 1960, to 5 mm y -1 afterwards (Frielinghaus and Vahrson 1998).…”
Section: Land-use Effects On Biodiversity In Sedimentsmentioning
confidence: 54%
See 1 more Smart Citation
“…The sedimentation rates previously estimated from two KH that are part of the present study (KH258 and KH807; Kleeberg et al, 2016) correspond to an average age of 15-30 years prior to this study in the upper 5 cm and to 50-100 years at 20 cm depth. These values are in line with previous studies in the area, which concluded that the sedimentation rate increased from 1-2 mm y -1 prior to 1960, to 5 mm y -1 afterwards (Frielinghaus and Vahrson 1998).…”
Section: Land-use Effects On Biodiversity In Sedimentsmentioning
confidence: 54%
“…Therefore, the sediment eDNA could well reflect community changes triggered by intensified agriculture. The separate clustering of eukaryotic phytoplankton from the upper and lower sediment, further suggests a recent change in communities in the last 20-30 years as dated by Kleeberg et al (2016). Coupling thin-layer sediment eDNA analysis with sediment dating in a large number of KH are needed to reinforce this tentative conclusion.…”
Section: Land-use Effects On Biodiversity In Sedimentsmentioning
confidence: 96%
“…Concentrations of K + , however, were greater than typical groundwater levels, and the kettle holes with shorter hydroperiods tended to have significantly greater concentrations relative to the longer hydroperiod kettle holes. Surrounding agricultural soils, especially clay rich horizons, are hypothesized to contribute to these elevated K levels through erosion and leaching (Gerke et al, ; Kleeberg, Neyen, Schkade, Kalettka, & Lischeid, ; Merz & Steidl, ), although we cannot explain why K + is retained longer and at higher concentrations within the kettle holes. In general, land managers have long recognized the heterogeneity in solute concentration and conductivity across the landscape by planting sugar beets in areas of high conductivity (Figure S1) and cornfields at higher elevations with lower conductivity.…”
Section: Discussionmentioning
confidence: 76%
“…At the slopes of the agriculturally intensively used Quillow river catchment, most of the former stratigraphic record has probably got lost, due to strong tillage activity since historic times (Sommer et al, 2008;Kleeberg et al, 2016). The only evidence of prehistoric slope processes was found in profile FKHG2, where a colluvial sand layer dated to 2466 ± 192 a.…”
Section: Late Holocene Soil Erosion In the Upper Ucker River Catchmentmentioning
confidence: 99%